The Relationship between Current COVID-19 and Indonesia Stock Market: Evidence from ARDL Model - Violita Septy Wardani; Lahuddin Lahuddin (Jurnal Ekonomi Pembangunan, 2021)
This study aims to prove how COVID-19 in response to the Indonesia stock market applying an Auto-Regressive Distributed Lag (ARDL) cointegration method. This study analyzes the relationship between the natural logarithm of daily trading volume of the Indonesia Stock Exchange and the natural logarithm of daily COVID-19 confirmed cases both in the short run and the long run. Bound test and cointegration were used to analyze the data daily from 2 March 2020 until 30 November 2020. The findings result show in the short-run, Indonesia stock market is only influenced by its lag, but not in the long-run. Meanwhile COVID-19 variable proved to be not significantly affected the stock market both in short and long-run. The model is predicted to re-stabilize at least over 1.7 months later